2022
DOI: 10.1155/2022/8238634
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Impact of Seeding Density and Nitrogen Rates on Forage Yield and Quality of Avena sativa L

Abstract: Green forage is an excellent feed source for livestock. It is an integral part of livestock production to accomplish the demands for butter, milk, and other derivatives for human utilization. Livestock contributes 11.39% towards the gross domestic product of Pakistan and 58.33% in agricultural farming. Livestock face shortage or insufficient supply of green fodder during the winter season, which ultimately reduces milk yield. Oat (Avena sativa L.) is a major forage crop in the winter season; however, several b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Some studies have found the effects of sowing density and nitrogen on crops. For example, Kanwal et al [33], by evaluating the effects of different sowing densities and nitrogen doses on oat forage yield, found that the interaction of sowing density and nitrogen amount significantly changed the yield and quality attributes of oat green forage. The sowing rate of forage oat crops should be 90 kg•ha −1 and supplemented with 120 kg•ha −1 nitrogen, producing a higher yield, better quality, and better return.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found the effects of sowing density and nitrogen on crops. For example, Kanwal et al [33], by evaluating the effects of different sowing densities and nitrogen doses on oat forage yield, found that the interaction of sowing density and nitrogen amount significantly changed the yield and quality attributes of oat green forage. The sowing rate of forage oat crops should be 90 kg•ha −1 and supplemented with 120 kg•ha −1 nitrogen, producing a higher yield, better quality, and better return.…”
Section: Discussionmentioning
confidence: 99%
“…Oat ( Avena sativa L.) is one of the world's most cultivated cool‐season forage cereal crops and provides a vital source of livestock feed (Fu et al, 2023). The widespread popularity of oats as a source of high‐quality forage can largely be attributed to their tolerance to cold, drought, and barren soils (Usman et al, 2018), as well as their high forage yield, good nutritional value, palatability, and digestibility (Kanwal et al, 2022). Approximately 74% of the world's oat production is used for forage, which is largely grown in high‐altitude and latitude areas (Liu & Mahmood, 2015; Ren et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%